PERANCANGAN SENSOR SWITCH PRINTER PRODUK SM5300X MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT UNTUK MENGATASI CUSTOMER COMPLAINT DI PT. TEB - Afma, Vera Methalina; Irwan, Hery; Ngadiyono, Ngadiyono (SIGMA TEKNIKA, 2023)
One of he problem at PT. TEB is that the assembly process for installing switches on the scale printer without using tools or jigs, and it causes the switch position is not correct because employees only use feeling and hearing when installing and causes undetectable rejects (Can Not Print). Other factor is installing the switch on the printer without using tools can also take quite a long time, resulting in the production of scales being of poor quality. The aim of this research is how to design tools to help install switches on printers using the Quality Function Deployment (QFD) method and it is also hoped that the results of this design make the quality of the scales is even better. Data collection was carried out by distributing questionnaires to 10 people consisting of operators, production leaders and also Quality Control. The results of data collection from the questionnaire showed that it was necessary to add an Assembly Switch Process to the Printer, namely by adding a jig switch. Therefore a new jig design can be used. The output produced after using the switch jig design increased by 68% and the rejected output decreased by 75% so it is considered that the new jig design can increase production results.